DEVELOPMENT OF AUGMENTED REALITY ON NEWTON’S LAWS TO REMEDIATE MISCONCEPTIONS AMONG PRE-SERVICE PHYSICS TEACHERS - Arif Wiratama; Susy Pransiska (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
Physics learning often faces challenges, particularly in helping students visualize and relate abstract concepts to real-world phenomena. To address this issue, this study investigates the theoretical validity, practical feasibility, and effectiveness of Augmented Reality (AR)-based learning media in remediating students’ misconceptions of Newton’s Laws. The study employed a research and development (R&D) design using the ADDIE model. Participants consisted of fifth-semester students enrolled in a Physics Education program. Data were collected through expert validation instruments, lecturer and student response questionnaires, and three-tier multiple-choice diagnostic tests. Qualitative data were analyzed to examine feedback and suggestions from experts, lecturers, and students, while quantitative data were analyzed to determine validity, user responses, and learning effectiveness. The results of expert validation indicate that the developed AR-based learning media meets the criteria of validity and feasibility for instructional use. Lecturer and student responses were classified as very good, with percentages of 86.72% and 89%, respectively. Furthermore, analysis of diagnostic test results shows a notable reduction in students’ misconceptions from pretest to posttest, with misconception levels decreasing to 71.3% at Tier 1, 45% at the combined Tier 1 and Tier 3, and 27.73% across all tiers. The effectiveness analysis further reveals that only 1–3 students (12.5%) continued to exhibit misconceptions after the intervention. These findings suggest that AR-based learning media can serve as an effective instructional tool for reducing students’ misconceptions of Newton’s Laws.